Antiproliferative Activity of Novel Imatinib Analogue as Potential Anticancer Agents, Synthesis and in vitro Screening - Sangwan, Kavita; Singh, Balvinder (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: A series of N-(2,5-dimethylphenyl)-4-pyridin-3-ylpyrimidin-2-amine derivatives were synthesized as Imatinib derivatives, bearing 2-chloroquinoline as a heteroaryl motif. Materials and Methods: The compounds were synthesized by reducing in situ prepared azomethine intermediate using NaBH4 as a reducing agent in methanol as a solvent. Fourier transformation-IR, proton-NMR along with mass spectrometry were used to determine the structures of the compounds. The antiproliferative activity of the compounds against cell lines A549 and MCF7 was evaluated in vitro using the MTT assay protocol. Results: The compounds showed moderate cell growth inhibition at a concentration of 10 µM. Among the test compounds, the compound with a dimethoxy group at the 6 and 8 positions of the 2-chloroquinoline ring displayed the highest antiproliferative activity. Conclusion: The synthesized Imatinib derivatives exhibited moderate antiproliferative activity against A549 and MCF7 cell lines, and the compound with a dimethoxy group at the 6 and 8 positions of the 2-chloroquinoline ring showed the highest activity. These findings suggest that further studies can be performed to optimize the antiproliferative activity of these compounds.
Keywords: Imatinib derivatives; Quinoline; Reducing amination; Antiproliferative activity